Pengaruh Intellectual Capital Terhadap Kinerja Karyawan Pada Badan Keuangan Dan Aset Daerah Kota Madiun - Ria Irmawati; Siti Suharni; Andri Hasmoro Kusumo Broto (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study investigates the impact of intellectual capital, comprising human capital, structural capital, and relational capital, on employee performance at the Badan Keuangan dan Aset Daerah (BKAD) Kota Madiun. The study's population and sample consist of 15 structural authorities from BKAD. The employed sampling technique is saturation sampling. This study employs a quantitative methodology, utilizing both primary and secondary data. Primary data were collected through questionnaires, while secondary data were sourced from documents, including personnel information and the organizational structure of BKAD. The investigation employed multiple linear regression, following a classical assumption test conducted using IBM SPSS v27 software. The results of this study indicate that human capital, structural capital, and relational capital simultaneously have a significant effect on the performance of BKAD employees. Partially, human capital and structural capital has a significant effect on the performance of BKAD employees, and relational capital does not have a significant effect on the performance of BKAD employees. It encompasses the knowledge, skills, and competencies of workers that augment organizational efficacy. Understanding this connection is crucial for enhancing productivity and achieving strategic goals.